Region-building in southern Africa : progress, problems and prospects - Sanders, Chris; Dzinesa, Gwinyayi A.; Nagar, Dawn. (London : Zed Books, 2012)
How successful have southern African states been in dealing with the major issues that have faced the region in recent years? What can be done to produce more cohesive and effective region-building in southern Africa? This original and wide-ranging volume, which draws on an interdisciplinary team of African and African-based specialists, addresses the key political, socio-economic and security challenges facing southern Africa today.
pt. 1. Historical legacy -- pt. 2. Governance and military security -- pt. 3. Economic integration -- pt. 4. Human security -- pt. 5. External actors.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Regionalism (International organization); Africa, Southern -- Politics and government -- 1994-; Régionalisme (Politique internationale); Afrique australe -- Politique et gouvernement -- 1994-; International relations; POLITICAL SCIENCE -- Political Ideologies -- Nationalism; Politics and government; Regionalism (International organization); Southern Africa; Since 1994